Anaerobic co-digestion of kitchen waste with hyperthermophilically pretreated grass for biohydrogen and biomethane production. (November 2022) - Liczbiński, Przemysław; Borowski, Sebastian; Cieciura-Włoch, Weronika
Graphical abstract: Highlights: Co-digestion of kitchen waste with grass at 55 °C produced 293 NmlCH4 /gVS. Methane yield from grass mono-digestion did not exceed 131 NmlCH4 /gVS. Digestion process at 35 °C turned into dark fermentation. Ruminococcaceae, Atopobiaceae and Lactobacillaceae families were found at 35 °C. Petrotogaceae, Synergistaceae and Methanosarcinaceae families were reported at 55 °C. Abstract: Anaerobic digestion of kitchen waste with grass after hyperthermophilic pretreatment was performed in semi-continuously operated reactors. The greatest methane yield of 293 NmlCH4 /gVS (volatile solids) was reported for the mixture of both substrates at 55 °C with a solids retention time of 30 d and the corresponding organic lading rate of 1.72 kgVS/m 3 /d. In contrast, pretreated grass subjected to thermophilic digestion produced only 131 NmlCH4 /gVS. However, when mesophilic conditions were applied, the digestion process turned into dark fermentation, especially visible for the mixture. Metagenomic analysis revealed the dominance Ruminococcaceae, Atopobiaceae and Lactobacillaceae at a family level in mesophilic processes, whereas Petrotogaceae, Synergistaceae, Hungateiclostridiaceae, Planococcaceae and two methanogens Methanosarcinaceae and Methanothermobacteriaceae were the most frequent microbes of thermophilic digestion. Kitchen waste can successfully be co-digested with hyperthermophilically pretreated grass at high loading rates, however the digesters must be operated at thermophilic temperatures.